Metabolic reprogramming in efferocytosis - Yan, Qing; Li, Kuo; Chen, Lu; Wang, Aowei; Xi, Yingying; Xiao, Hui; Yuan, Lei (Frontiers in Cell and Developmental Biology, 2025)
Efferocytosis refers to the process by which phagocytes specifically identify and eliminate apoptotic cells. This process is essential for both maintaining tissue homeostasis and suppressing inflammatory responses, as well as facilitating tissue repair. When phagocytes internalize apoptotic cells, which act as “nutrient packages,” they undergo significant metabolic reprogramming. This reprogramming not only supplies energy and biosynthetic precursors necessary for engulfment but also critically influences the functional phenotype of phagocytes through complex molecular networks. These networks ultimately determine whether phagocytes adopt an anti-inflammatory resolution or a pathological pro-inflammatory state. This article offers a comprehensive analysis of the molecular regulatory mechanisms that underpin metabolic reprogramming during efferocytosis, aiming to elucidate the intricate regulatory networks formed by the interaction of metabolites as signaling molecules and classical signaling pathways. We examine how the three primary metabolic pathways—glucose, lipid, and amino acid metabolisms—are regulated by signals from efferocytosis and, in turn, modulate phagocyte function. A deeper understanding of the interplay between metabolic reprogramming and efferocytosis will provide a theoretical foundation and novel targets for treating diseases associated with impaired clearance of apoptotic cells.